Microbial community shifts drive biodegradable microplastic inhibition of seed germination in plateau wetlands - Hong Xiang; Jia-Xian Luo; Hao-Ran Bao; Xiao-Long Sun; Hao-Qin Xiong (Ecotoxicology and Environmental Safety, 2025)
This study elucidates the mechanistic role of microplastic (MPs)-induced microbial shifts in suppressing soil seed bank functionality within plateau wetlands. A greenhouse soil pot experiment was designed to examine the impact of varying MPs particle sizes and concentrations. The findings revealed that the group treated with biodegradable MPs (polybutylene succinate-PBS) exhibited the most potent inhibition of seed germination. Specifically, treatments with polyethylene-PE yielded a minimum of 54 seedlings, contrasting sharply with the PBS group, which produced only 24 seedlings under comparable conditions. Dominant germinating species (Poaceae/Cyperaceae) declined sharply under PBS exposure. Echinochloa caudata germination fell to fewer than 20 seedlings (vs. 30 under PE), while species richness dropped to 7–9 species (vs. 10–15 under PE). Soil chemical properties, notably total nitrogen, nitrate-nitrogen, and soil organic carbon, experienced significant changes. These alterations in soil chemistry had a cascading effect on the composition of germinating species. In the MPs treatment groups, abundance of Proteobacteria, Actinobacteria, and Bacteroidetes bacteria increased. Multivariate analyses using nonmetric multidimensional scaling and linear discriminant analysis effect size demonstrated that biodegradable MPs exerted a more substantial influence on microbial community structure, thus altering the species composition of the seed bank. Mantel tests further indicated a significant correlation between changes in microbial community structure and the prevalence of dominant plant families, particularly Poaceae and Cyperaceae.